Diagnostic and Prognostic Role of Liver Elastography in Heart Failure - Ávila,Diane Xavier (2020)
Abstract Background: Hepatic congestion is a frequent finding in patients with heart failure (HF). Physical examination has limitations in quantifying systemic congestion and requires correlation with echocardiographic and laboratory data (usually B-type natriuretic peptide, BNP, or N-terminal pro-B type natriuretic peptide, NT-proBNP). Hepatic elastography evaluates liver stiffness using a transducer that transmits low-frequency vibrations (50 Hz), and the speed of shear waves propagating through the tissues is measured by ultrasound. The faster the vibrations propagate in the hepatic parenchyma, the stiffer the liver, which, in case of HF, can be correlated with hepatic congestion. Objective: In this systematic review, case-controls, cohort studies, and randomized clinical trials were searched in MEDLINE, LILACS and Cochrane Database of Systematic Review, to evaluate the use of elastography in the detection of hepatic congestion in patients with HF. Methods: From the 49 articles retrieved, seven were selected for review, according to the inclusion and exclusion criteria. The most used methods for the diagnosis and evaluation of HF were echocardiography combined with BNP and NT-proBNP measurements. Results: Elastography performed at bedside was able to establish a significant correlation between increased liver stiffness and increased venous capillary pressure. In addition, liver elastography performed at hospital discharge was able to predict rehospitalization and mortality. Conclusion: Liver elastography is a non-invasive method that can be useful in predicting prognosis and mortality of individuals with HF, contributing to the clinical management of these patients.